Improving the Ability to Read Biographical Texts Through a Student Process Approach - Rajatman; Kastam Syamsi (UNIVERSITAS PAKUAN, 2025)
This study aims to find out the improvement of the learning process in reading biographical texts through the process approach and the improvement of the results of the ability to read biographical texts through the process approach method in students. The method used in this study is a process approach. The subjects taken were 35 students in class X DKV B SMK Negeri 1 Nunukan. This Classroom Action Research is carried out with a process approach The steps taken in reading learning through a process approach, namely the preparation stage are (1) choosing the text; (2) relate the text to personal experience and previous reading experience; (3) predict the content of the text; and (4) conduct a preliminary review of the text. There is a second stage, namely reading, students read the text in its entirety. In the third stage, responding, students respond to their reading activities and continue to try to understand the content. Data collection uses documentation, interviews, observations and tests. The data analysis techniques used in this study are descriptive statistical analysis and quantitative data are analyzed with a flow model. The results of this study concluded that the process approach of increasing interest and reading ability to read biographical texts was seen from 34 students whose interest increased from cycle to cycle, both those whose students' interest was classified as less to sufficient, from sufficient to high, or from high to very high. It can also be seen that only one student whose interest has not increased. (2) The process approach is able to improve the ability to read biographical texts as evidenced by the initial conditions, cycle I, and cycle II, there are 28 students or around (75%) whose grades increase from cycle to cycle, there are 3 students whose grades are fixed, and there are 4 students whose grades decrease.